PREDIABETES - MODERN ENTITY WITH NUMEROUS RISK FACTORS - Marjanović Petković, Milica (Medicinski podmladak, 2023)
Prediabetes (PreDM), the seventh leading cause of mortality, is constantly on the rise. It isestimated that by 2035, the number of people affected by prediabetes will reach 471 millionpeople of the total population. Whether a person with prediabetes will develop type 2diabetes within the next year, or later, or maybe never, depends on numerous factors, some ofwhich are modifiable (body mass index (BMI), waist circumference (WC), lipid status,smoking habits, physical activity). If a person measures postprandial blood glucose levelshigher than 7,8 mmol/L, they have twice the cardiovascular risk compared to someone withnormal glycemic control. Hyperinsulinemia causes insulin resistance and endothelialdysfunction, while hyperglycemia leads to oxidative radicals forming and activatingproinflammatory cytokines. Prediabetes is often associated with obesity and lipid disorders,which further contribute to elevated cardiovascular (CV) risk in individuals with prediabetes.There is a significant number of undiagnosed individuals with prediabetes. Therefore,screening all individuals with risk factors, including proper screening measures such ascoronary artery calcium (CAC) scoring, is crucial to assess and prevent cardiovascular risk. Itis important to correct all risk factors, achieve normoglycemia in patients with mildlyelevated blood glucose levels, initiate pharmacotherapy at the right time, and as a result,reduce the risk of cardiovascular diseases, cerebrovascular diseases, chronic kidney disease,cancer, and dementia.
Keywords: prediabetes; cardiovascular risk; coronary artery calcification